Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1177/0192623309348521
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipidosis in Neurons Caused by Posaconazole, without Evidence for Functional Neurologic Effects

Abstract: The azole antifungal drug posaconazole caused phospholipidosis in neurons of the central nervous system, dorsal root ganglia of the spinal cord, and myenteric plexus in chronic toxicity studies in dogs. The time of onset, light and electron microscopic features, neurologic and electrophysiologic effects on the central and peripheral nervous systems, and potential for regression were investigated in a series of studies with a duration of up to one year. Nuclei of the medulla oblongata were the prominently affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Although the brain is a less commonly reported site of DIPL, azithromycin, chloroquine, quinacrine, 4,4′-diethylaminoethoxyhexestrol, chlorphentermine, iprindole, 1-chloro-amitriptyline, clomipramine, perhexiline, and fenfluramine have all been reported to cause DIPL in the rat brain and/or peripheral ganglia (Dastur et al, 1985;Frish and Lüllmann-Rauch, 1980;Lüllmann-Rauch, 1976;Jung and Suzuki, 1978). Posaconazole caused DIPL in the neurons of the CNS, dorsal root ganglia of the spinal cord and myenteric plexus in a toxicity study in dogs (Cartwright et al, 2009). In dogs treated with posaconazole, neurons contained multi-lamellar bodies and some axons in the brain and spinal cord were swollen and contained granular eosinophilic, electron dense lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the brain is a less commonly reported site of DIPL, azithromycin, chloroquine, quinacrine, 4,4′-diethylaminoethoxyhexestrol, chlorphentermine, iprindole, 1-chloro-amitriptyline, clomipramine, perhexiline, and fenfluramine have all been reported to cause DIPL in the rat brain and/or peripheral ganglia (Dastur et al, 1985;Frish and Lüllmann-Rauch, 1980;Lüllmann-Rauch, 1976;Jung and Suzuki, 1978). Posaconazole caused DIPL in the neurons of the CNS, dorsal root ganglia of the spinal cord and myenteric plexus in a toxicity study in dogs (Cartwright et al, 2009). In dogs treated with posaconazole, neurons contained multi-lamellar bodies and some axons in the brain and spinal cord were swollen and contained granular eosinophilic, electron dense lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Posaconazole also binds CYP46A1 and may therefore also inhibit these pathways (7,8). Moreover, phospholipidosis due to membrane accumulation of posaconazole has been reported (9). Although central nervous system (CNS) toxicity has not previously been reported with posaconazole, this observation may reflect the low levels achieved with the oral suspension combined with its low CNS penetration (7,10).…”
mentioning
confidence: 99%
“…Clearly, there are differences in the physical and chemical properties between AZD3783 and these aforementioned CADs that contributed to the differences in the toxicity and pathologic findings in the nervous tissues. One notable difference is that, in the study with posaconazole 28 inflammatory changes were not observed in any tissues with PLD. In contrast, in our studies with AZD3783, inflammation and gliosis was present in the nervous tissue (eye, ganglion, and brain).…”
Section: Discussionmentioning
confidence: 62%
“…Among the non-CNS drugs, posaconazole (an antifungal) caused PLD in DRG and medulla oblongata neurons in the brain of dogs after chronic administration. However, there was no evidence of neuronal degeneration or necrosis, nor was there any alteration in the amplitude, or latency of the auditory, visual, or somatosensory evoked potentials 28 . Clearly, there are differences in the physical and chemical properties between AZD3783 and these aforementioned CADs that contributed to the differences in the toxicity and pathologic findings in the nervous tissues.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation